1990
DOI: 10.1056/nejm199004263221705
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Features of Adrenocortical Carcinoma, Prognostic Factors, and the Effect of Mitotane Therapy

Abstract: Adrenocortical carcinoma is a rare tumor, and only limited information is available about its natural history and the effects of therapy. We studied 105 patients (75 female and 30 male; mean age, 46 years) with adrenocortical carcinoma who were referred to us between 1963 and 1987. The average duration of symptoms before diagnosis was 8.7 months. At the time of diagnosis, 68 percent of the patients had endocrine symptoms, and 30 percent had distant metastases. Hormonal studies showed that 79 percent of the tum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

21
395
1
22

Year Published

1991
1991
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 637 publications
(439 citation statements)
references
References 53 publications
21
395
1
22
Order By: Relevance
“…Adrenocortical carcinoma (ACC) is a rare malignant tumour with a poor prognosis (Hutter and Kayhoe, 1966;Bertagna and Orth, 1981;Didolkar et al 1981;Luton et al, 1990). An aggressive surgical approach provides disease control for the minority of patients presenting with localized disease.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Adrenocortical carcinoma (ACC) is a rare malignant tumour with a poor prognosis (Hutter and Kayhoe, 1966;Bertagna and Orth, 1981;Didolkar et al 1981;Luton et al, 1990). An aggressive surgical approach provides disease control for the minority of patients presenting with localized disease.…”
mentioning
confidence: 99%
“…An aggressive surgical approach provides disease control for the minority of patients presenting with localized disease. In patients with advanced disease, survival is < 50% at I year and < 10% at 5 years (Luton et al, 1990;Jensen et al, 1991;Icard et al, 1992;Pommier and Brennan, 1992).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…12 Feller et al reported that treatment with a combination of multiple-resistance drugs plus mitotane yielded no significant effects in vivo. 1 Therefore, we must analyze the oncogenesis of adrenocortical carcinoma more deeply and develop a good model to help us establish an effective new treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Approximately 60% of ACCs are functional tumors [2]. Patients can present with Cushing's syndrome alone (45%), a mixed Cushing's and virilization syndrome (25%), or virilization alone (< 10%) [3].…”
Section: Introductionmentioning
confidence: 99%